(untitled) (Research, Society and Development, 2022)
The objective was to analyze the impact of ostomies on the sexual function of ostomized women. Analytical, cross-sectional, quantitative study carried out at the Stomatherapy Outpatient Clinic of the University Hospital of the Federal University of Maranhão. The sample consisted of 44 women with temporary or permanent elimination stomas. Two questionnaires were used, one with sociodemographic, economic, clinical, housing and lifestyle data prepared by the authors, and the second with the Female Sexual Quotient (QS-F) to assess sexual activity. The Shapiro Wilk tests were used to verify the normality of continuous variables, Student’s t test for analysis of dichotomous variables, the Anova Oneway factor or the Kruskal Wallis nonparametric test for polytomous variables and Pearson’s linear correlation for continuous variables. Results with p < 0.05 were considered statistically significant. Few women had a good or excellent sexual pattern (15.91%). The sample’s mean QS-F score was 39.13 (±29.37). Regarding associations, older age (r -0.32, p = 0.029), arterial hypertension (t = -21.39, p = 0.017), diabetes (t = -29.85, p = 0.025) and alcohol consumption alcoholics (t = -24.44, p = 0.039) had lower QS-F scores. A low level of women’s sexual performance and the presence of sexual dysfunctions were found. An inverse relationship between age and sexual function was observed. The variables arterial hypertension, diabetes and drinking habits were significantly associated with impairment in the participants’ sexual performance.